Inner retinal thickening affects microperimetry thresholds in the presence of photoreceptor thinning in patients with RPGR retinitis pigmentosa. Issue 2 (30th October 2020) - Jolly, Jasleen Kaur; Menghini, Moreno; Johal, Piers A; Buckley, Thomas M W; Bridge, Holly; Maclaren, Robert E
Abstract : Background: Loss of photoreceptors cause degeneration in areas of the retina beyond the photoreceptors. The pattern of changes has implications for disease monitoring and measurement of functional changes. The aim of the study was to study the changes in inner retinal structure associated with photoreceptor disease, and the impact of these on microperimetry threshold. Methods: This retrospective cohort study was conducted on optical coherence tomography (OCT) images and microperimetry tests collected between 2013 and 2019. 22 eyes with RPGR retinitis pigmentosa completed both OCT imaging and microperimetry assessment. 18 control eyes underwent OCT imaging. Photoreceptor layer and inner retinal thickness calculated for different eccentric areas were obtained. The relationship between the photoreceptor layer and inner retinal thickness, and microperimetry threshold was explored. Results: Central 1° photoreceptor layer and inner retinal thickness were 96±34 and 139±75 μm in RPGR patients, and 139±15 and 62±14 μm in controls. Photoreceptor layer thickness differed between patient and control groups across increasing visual field areas (p<0.01, Kruskal-Wallis 1-way ANOVA), whereas the inner retinal thickness significantly differed between groups for the central 1° and 3° only. Microperimetry thresholds were explained by a combination of photoreceptor thickness (coefficient 0.15, 95% CI 0.13 to 0.18) and inner retinal thickness (coefficient 0.05, 95% CI 0.03 to 0.06). Conclusion: OCT shows evidence of remodelling in the inner retinal layers secondary to photoreceptor disease. This appears to have an impact on microperimetry threshold measurements.